The safety helium collectors for the ESS superconducting linac: functional specification and detailed design. (April 2019) - Fydrych, J; Lundh, E; Moberg, J; Phan, D; Tereszkowski, P; Weisend, J G II
Abstract: The ESS proton linac includes 43 separate cryomodules which are cooled down by means of a saturated superfluid helium bath. For safety reasons, access to the machine is limited and strictly controlled. However, this does not exclude some oxygen deficiency hazards. In order to prevent exposure of personnel to helium releases during access to the tunnel (Beam OFF mode), it was decided to equip the machine with two safety helium collectors, which are intended to collect the helium released by the burst disks of the cryomodule 2 K helium vessels, in case of an accidental event and vent it outside the tunnel. However, in Beam ON mode, when more than one cryomodule can discharge cold helium at the same time, the collectors must not cause any significant back pressure to the burst disks or cavities. The paper presents the functional specification, feasibility study and design of the safety helium collectors.